Perceptions and practices of rural Indian women in contraception, abortion, and sexual health: a cross sectional study - Davis, Amenda Ann (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal mortality is an important target of health care policies, especially in India. While numerical indicators of maternal health improve, this can only be sustained with change in the knowledge, attitudes, and practices of women. Gender empowerment is a neglected aspect of health care policy, and there is a need to assess the perceptions of Indian women, the true torch-bearers of change. Methods: This was a hospital based cross sectional quasi-quantitative study in a sub-district hospital in the town of Ballabgarh, Haryana, India. Married women attending the outpatient clinic, antenatal clinic, labor ward, and primary health centres in the age group of 20 to 40 years were interviewed using a semi-structured questionnaire with both closed and open-ended questions. Health concerns were concurrently addressed. Results: Author interviewed 956 women. No form of modern contraception had ever been used by 58.36% of the women. Intra-uterine contraceptive devices were discontinued by 76.12% of the women who had used them. Emergency contraception was a concept known to 49.89% of the women, but fraught with misconceptions. Induced abortions was being used as a form of family planning, with nearly 90% of the women having taken over-the-counter abortifacients. Women were receptive to contraception, and many expressed an interest in long acting contraceptives other than IUCDs. Conclusions: This study provides insight into the thinking of Indian women regarding family planning. This may help guide family planning policies.